A study of theme and technique in the creative works of S.E.K.L.N. Mqhayi - Qangule, Zitobile Sunshine (African Languages and Literatures, 2017)
S.E.K. Mqhayi has been declared the most successful of all the modern Xhosa writers. He has been proclaimed "The Shakespeare of the Xhosa language". The showering of such praises upon a man have prompted us to study some of his major views about life and the manner of expressing these. * The first chapter deals with the formative influences which played a prominent part in Mqhayi's literary creativity. These are: the home, the school and the church. The portrayal of the man is made more explicit by citing what literary critics in general, and Xhosa poets in particular, have said about Mqhayi. A list of Mqhayi's published works and various comments on these add dimension to his stature. The chapter ends with a brief outline of the development of thought in Mqhayi's works. It is pointed out that each principal thought or major theme constitutes a chapter of this thesis. The first chapter serves as a thread that knits the different chapters together. * The second chapter is a study of Mqhayi's views on the nature and operation of law in Xhosa traditional society. The various techniques employed by Mqhayi in articulating his views are pointed out. Mqhayi intimates in his works that law functions in a Xhosa traditional society in a manner similar to the operation of law in modern society. we have supported Mqhayi's contentions by drawing parallels with the western legal system. It is emphasized in this chapter that "the traditional Xhosa legal system is an integral part of the Xhosa religious order". The idea that Xhosas and other Black races had no laws governing them prior to contact with Whites is refuted by conclusive argument. * Chapter three is a discussion of Mqhayi's serious concern about disunity and a lack of socio-political advancement among the Blacks of South Africa and the breaking down of law and order among the Xhosa people in general and among the various Black races in particular. The reader's attention is drawn also to Mqhayi's concern about deteriorating relations between Blacks and Whites in South Africa. We show how the author offers solutions to these grave problems. Towards the end of the chapter, Mqhayi emerges as a patriot and a humanist. * The concept of patriotism receives attention in chapter four. Biographical sketches of various Black and White leaders whom Mqhayi regarded as patriots are given. These biographies help in interpreting the poems written by Mqhayi about the said patriots. Of great interest to the reader should be the various devices employed by the poet in revealing patriotic action. A consistent and comforting note in most of the poems is the assurance that the patriots who departed from this earth are alive and active in the spiritual world. * Throughout his works Mqhayi denigrates undesirable characters and deprecates evil actions or situations. This is brought out in sharper focus in chapter five. The various techniques he uses are mentioned and discussed. The reader's attention is drawn to the following: (a) virtue is extolled in Mqhayi's writings; (b) the author "preaches the gospel of hope and faith in human progress". Thus, brief notes on the transformation of the undesirable characters bring the chapter to an end. * Literary critics will always point out what they consider as merits or demerits in a man's creative work(s). Chapter six deals with a critical appraisal of criticisms levelled against Mqhayi as a literary artist. The validity or otherwise of the opinions expressed is discussed. * Chapter seven is a general conclusion. The main observations are summarised and suggestions for further studies are indicated. * It is hoped that the entire study will serve as a design or model for understanding the creative works of S.E.K.L.N. Mqhayi. For additional information on the possible value of this study, the literary critic is referred to chapter seven (pages 249-254).